Third generation perspectives on the holocaust in Everything is illuminated, by Jonathan Safran Foer, and its film adaptation, by Liev Schreiber - Silva, Emanuelle Schok Melo da (2019)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão, Programa de Pós-Graduação em Inglês: Estudos Linguísticos e Literários, Florianópolis, 2019.